Pengaruh Harga, Kualitas Pelayanan, Dan Lokasi Terhadap Loyalitas Pelanggan Bento Kopi Cabang Godean - veronicha, shinta aulia; Krisna Mutiara Wati (PT. Karya Inovatif Nusantara, 2024)
Rapid growth and development has occurred in coffee shops in the Special Region of Yogyakarta. Bento Kopi Godean branch is one of the coffee shops that continues to survive and develop when many coffee shops are currently established. The strategy to win the competition with competitors is to create and maintain customer loyalty. This study is to determine the effect of price, service quality, and location on customer loyalty of Bento Kopi Godean branch. This type of quantitative research uses a purposive sampling method and a sample size of 100 respondents distributed via Google Form. Data analysis used SmartPLS software version 4.0. Based on the results of the study, it states that price has a t-statistic of 4.087 > 1.96 and a p-value of 0.000 < 0.05, service quality has a t-statistic of 2.079 > 1.96 and a p-value of 0.036 < 0.05, and location has a t-statistic of 2.3352 > 1.96 and a p-value of 0.019 < 0.05. It is concluded that price, service quality, and location have a positive and significant effect partially on customer loyalty of Bento Kopi Godean branch.